HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN KEBERHASILAN PENYAPIHAN VENTILASI MEKANIK DI RUANG ICU - Anari, Afie; Rachman, Aulia; Lanawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2025)
Background: Pulmonary TB can be a significant stressor, increasing stress potential in patients. The clinical manifestations of TB and the prolonged, intensive treatment with antituberculosis drugs (ATD) can develop into sources of stress, potentially worsening the patient's overall stress. This stress may negatively impact disease and treatment management, leading to a reduced quality of life. Purpose: This study aims to assess stress levels among pulmonary TB patients. Methods: A quantitative approach with a descriptive survey design was employed. Data were collected using the Perceived Stress Scale (PSS)-10 questionnaire among 30 pulmonary TB patients at a community health center in Banjarmasin City. Data analysis used univariate methods with frequency distribution calculations. Result: Findings indicate that 93.3% of pulmonary TB patients experienced moderate stress levels, with two primary stress-inducing factors: uncertainty/anxiety and a sense of helplessness Implication: This study emphasizes the importance of a holistic approach to pulmonary TB management, addressing both physical and psychosocial aspects.